Repurposing of mine waste: an alternative management approach to gold tailings in South Africa - Sibanda, Lesley Kudakwashe (Department of Chemical Engineering, 2020)
The large volumes of waste generated during gold beneficiation are a major pollution concern in South Africa. To remove these potential pollution risks in perpetuity, non-conventional approaches to mine waste management are required which avoid land disposal of “unwanted” material. This dissertation explores the opportunities, drivers and barriers for the re-purposing of gold tailings in South Africa. The thesis draws on a comprehensive literature review, analysis of information and data in the public domain, and semi-structured interviews with relevant experts. The research findings identified numerous potential uses for gold tailings including reusing gold mine tailings in making bricks, ceramics, cement additives, backfill, stone paper and aggregate material for construction. The derelict tailing dumps can also be used for recreation purposes, tourism and many other land use applications. The study showed that despite existing opportunities, the application of mine waste as feedstock for other purposes in South Africa is currently constrained. According to the findings, this can be credited to numerous inter-related factors, such as inadequate technology development, lack of an enabling legislative framework, high short-term costs, and potential environmental risks associated with hazardous components in the waste. Overcoming these barriers will require innovative, transdisciplinary approaches, and effective partnerships with relevant stakeholders, including academia, private business entities (waste users) and regulatory bodies (government).